Monetary Policy Autonomy in the CFA Franc Zone: Comparative Insights from Francophone and Non-francophone African Economies - (:unkn) unknown (My University, 2024)
This study analysed the experiences of 14 CFA zone African countries with that of 12 other African countries and investigated the potential implications of monetary autonomy in the CFA zone using a panel dataset spanning from 1990 to 2023. To assess the relative monetary flexibility in the CFA zone, the study employs a country-by-country ARIMA model on money supply and exchange rate and obtain their flexibility components. Given the two transition variables: exchange rate flexibility and monetary policy flexibility, Dynamic Stochastic General Equilibrium (DSGE) and Panel Smooth Transition Regression (PSTR) models were then applied to the data to assess the implications of monetary autonomy on CFA zone countries. The DSGE model indicates a high degree of interest rate smoothing suggesting that the central banks (BEAC and BCEAO) face challenges in adjusting the nominal interest rate quickly in response to changing macroeconomic economic conditions. The findings from the PSTR indicate that in a less flexible monetary and exchange rate environment household consumption is responsive to changes in traditional macroeconomic factors like wages, capital, taxes, and inflation. In a more flexible monetary and exchange rate environment, the magnitudes of the effects of these macroeconomic factors on household consumption are generally larger. In the more flexible regime, the positive impact of investment, capital, and government spending on economic growth is more pronounced, while the negative impact of taxation is more severe. The transition between the two regimes is governed by smooth thresholds with a rapid transition as the thresholds are crossed. The study recommends that Francophone African countries transition to an autonomous monetary policy framework to enhance economic growth by addressing unique challenges like inflation and exchange rates. A phased approach based on Optimum Currency Area theory is essential, emphasising regional integration and inst
Keywords: African Research